PENGARUH PENDAPATAN PREMI, HASIL INVESTASI, HASIL UNDERWRITING DAN RISK BASED’CAPITAL TERHADAP PROFITABILITAS PERUSAHAAN ASURANSI (STUDY EMPIRIS PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2019) - Retno Setyaningsih; Yulita Zanaria; Ana Septiani (Jurnal Akuntansi AKTIVA, 2021)
This study aimed to examine the factors that affect the profitability of insurance companies on the Indonesia Stock Exchange 2012-2019 period. The factors that affected the profitability of insurance companies on the Indonesia Stock Exchange were premium income, investment returns, underwriting results and risk based capital. This study used a quantitative approach. The population in this study were 16 insurance companies on the Indonesia Stock Exchange. The sampling technique used purposive sampling method with certain criteria in order to obtain a sample of 8 insurance companies. The data in this study were analyzed using the help of IBM SPSS version 20 by testing multiple linear regression analysis. The results of this study indicated that the premium income and underwriting results partially affected the profitability of insurance companies. Meanwhile, investment returns and risk based capital partially did not affect the profitability of insurance companies. As well as premium income, investment returns, underwriting results and risk based capital simultaneously affected the profitability of insurance companies.